Does institutional quality affect firm performance? Insights from a semiparametric approach - Sumon K. Bhaumik; Ralitza Dimova; Subal C. Kumbhakar; Kai Sun (Institute for the Study of Labor (IZA), 2012)
Using a novel modeling approach, and cross-country firm level data for the textiles industry, we examine the impact of institutional quality on firm performance. Our methodology allows us to estimate the marginal impact of institutional quality on productivity of each firm. Our results bring into question conventional wisdom about the desirable characteristics of market institutions, which is based on empirical evidence about the impact of institutional quality on the average firm. We demonstrate, for example, that once both the direct impact of a change in institutional quality on total factor productivity and the indirect impact through changes in efficiency of use of factor inputs are taken into account, an increase in labor market rigidity may have a positive impact on firm output, at least for some firms. We also demonstrate that there are significant intra-country variations in the marginal impact of institutional quality, such that the characteristics of winners and losers will have to be taken into account before policy is introduced to change institutional quality in any direction.
urn:nbn:de:101:1-201205026175
Keywords: C14; D24; K31; O43; 330; institutional quality; firm performance; marginal effect; textiles industry